ACTIVITY OF INHIBITING THE GROWTH OF STAPHYLOCOCCUS AUREUS ATCC 25923 LEAVES OF DURI SPINACH (AMARANTHUS SPINOSUS LINN. ) USING THE MACERATION METHOD - Fitriawati, Anna; Lestari, Vera Fuji; Dwi S, Anita (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Antibacterial is a substance that can inhibit or kill the growth of bacteria. One of the plants that can be used for antibacterial is spinach thorns. Spinach (Amaranthus spinosus Linn.) is a plant originating from the tropical lowlands of America, widely distributed in the tropics and subtropics of Africa, Southeast Asia and in India and even in Indonesia. The purpose of this study was to determine the activity of spinach leaves (Amaranthus spinosus Linn.) on inhibiting the growth of Staphylococcus aureus bacteria by maceration method. This study uses an experimental method. Spinach leaves (Amaranthus spinosus Linn.) were macerated using 70% ethanol solvent. The concentrations used for each method were concentrations of 30%, 40%, 50%, ciprofloxacin positive control and 1% DMSO negative control. Each of these concentrations was tested for antibacterial activity against Staphylococcus aureus using the diffusion and dilution method. The results of the antibacterial activity test by diffusion in the maceration method obtained an average inhibition zone result at a concentration of 30% of 8.73mm, a concentration of 40% of 9.93mm, a concentration of 50% of 11.53mm and a positive control of 12.73mm.